Pogostost kromosomskih nepravilnosti pri otrocih, rojenih z biomedicinsko pomočjo - Korošec, Sara (Medicinski razgledi, 2001)
Background. Despite doubts about safety of in vitro fertilisation-embryo transfer (IVF-ET), intracytoplasmic sperm injection (ICSI) and use of frozen embryos, statistical analyses up to date have shown that risk of congenital malfomations is not essentially different from the risk in case of natural conception. The only fact that was shown is that in neonates born after ICSI procedure, abnormalities of sex chromosomes were present more often. Risk factors of sterile couples are: their age, sterility and frequent multiple pregnancies. An assessment of prevalence and distribution of chromosomal and structural malformations in our country would be useful in treating the sterile couples in the future.Aim and hypothesis. The aim of the survey is to determine whether rates of congenital malformations in neonates born after assisted reproductive techniques are higher than in neonates born after a spontaneous conception.Patients and methods. 242,164 neonates born to 241,607 mothers from April 1987 to December 1997 in Slovenia, were included in retrospective survey. The survey was divided into 3 cohort and 1 case-controlled studies. In first two studies prevalence of chromosomal, structural and lethal abnormalities were observed. In first study we compared 1404 neonates born after IVF-ET procedure with neonates born after spontaneousconception. In second controlled study we compared 1270 neonates born after IVF-ET procedure with 1270 neonates born after spontaneous conception, whose mothers were matched according to their age, multiplicity, parity and year of birth. In third study we observing the shares of congenitalabnormality rates according to a form of fertilisation. We compared 73 neonates with congenital abnormalities, born after IVF-ET procedure with 9685 neonates with congenital abnormalities, born after spontaneous conception. (Abstract truncated at 2000 characters)
Keywords: Chromosome abnormalities; porodništvo; oploditev; Epidemiology; fertilization; Diagnosis; zunajtelesna oploditev; kromosomske nepravilnosti; Fertilization in vitro; Embryo transfer; Infant, newborn; Ovulation induction; Risk factors